Pengembangan Handmade Masker Untuk Pemberdayaan Ekonomi Masyarakat Gresik Menghadapi Pandemi Covid-19 - Darni; Udjang Pairin; Surana; Latif Nur Hasan; Noviyanti; Yuni Lestari (LPPM Universitas Yudharta Pasuruan, 2020)
The COVID-19 pandemic has spread to all countries in the world. It is not only the nature of the corona virus that has extraordinary spreadability, but this viral pandemic also has an extraordinary impact on all sectors of life. The drastic decline in income, especially for the middle to lower class, was the biggest hit, starting from the loss of income, the non-return of capital, to layoffs. So many government policies have been issued as government strategies in preventing the spread, handling, and efforts to break the chain of COVID-19. Appeals have been issued by the central government to remain calm amidst these extremely difficult circumstances. The word "calm" here means not to panic excessively and to remain vigilant. The government has made efforts to prevent the spread of COVID-19, including by issuing a policy of wearing masks for people with COVID-19 and people in good health. The use of masks for the general public will of course be different from the masks used by medical personnel. Ordinary masks or handmade masks can be used to prevent the spread of the virus. This community service activity (PKM) has objectives, including: carrying out empowerment activities for people affected by COVID-19, so that it has an impact on improving income for the affected community. Unesa's PKM activities are also a form of Unesa's steps to work together with the government or partners to make efforts to prevent / prevent the spread of COVID-19.